Farming, growing up on a farm, and haematological cancer mortality. Issue 2 (27th July 2011) - Mannetje, Andrea 't; Eng, Amanda; Pearce, Neil
Abstract : Objectives: Occupation as a farmer has been associated with increased risks of haematological cancers in adults. This study aimed to examine whether farm exposures in childhood contribute to these risks, by using parental occupation in farming as a proxy for growing up on a farm. Methods: New Zealand death records (1998-2003) of persons aged 35-85 were extracted (n=114 289). For 82.3% usual occupation and the occupation of at least one of the parents could be coded (n=94 054). Unconditional logistic regression analyses included 3119 haematological cancer deaths (cases) and 90 935 deaths from other causes (controls). ORs for farming and growing up on a farm were adjusted for each other, year of birth, age at death, socio-economic status, Māori ethnicity, immigration status and sex. Results: Growing up on a livestock farm was positively associated with haematological cancer (OR 1.22, 95% CI 1.05 to 1.41), particularly for poultry farms (OR 2.99, 95% CI 1.44 to 6.21), while growing up on a crop farm was not (OR 0.81, 95% CI 0.64 to 1.03). Crop farming in adulthood was associated with an increased haematological cancer risk (OR 1.49, 95% CI 1.13 to 1.96), while livestock farming was not (OR 0.80, 95% CI 0.63 to 1.00), except for beef cattle farming (OR 2.99, 95% CI 1.28 to 7.00). These results did not change appreciably when different control groups with different causes of death were used. Conclusions: These results could suggest a role for early life biological exposures in the development of haematological cancers.